Evaluasi Manajemen Risiko Teknologi Informasi pada Badan Perencanaan, Penelitian dan Pengembangan (Barenlitbang) Kota Malang Menggunakan Cobit 5 Domain EDM03 dan APO12 - Agatha Shella Agtika; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Information technology (IT) risk management evaluation at Badan Perencanaan, Penelitian dan Pengembangan (BARENLITBANG) city of Malang is needed because the current implementation is not yet optimal. One of the reasons is the absence of particular division that manages IT risk at BARENLITBANG. In this research, the framework Control Objective for Information and related Technology 5 (COBIT 5) is used to evaluate and assess the capability level of the IT risk management at BARENLITBANG. The domains used are EDM03 (risk optimization) and APO12 (risk management). This research begins with data collection, then analyzing capability levels and gap, identificating the risk using the Risk Breakdown Structure (RBS), assess the risk, and making mitigation and recommendations. Results of the capability level in EDM03 domain is level 1 while domain APO12 is in level 2 with 1 level gap for both domains. From 9 identified risks, there are 5 risks in the middle category and needed to be mitigated while 4 risks in low category can be accepted by the organization. There are 6 recommendations recommended for BARENLITBANG such as making SOP to regulate risk management, optimizing supervision and evaluation, making risk maps, maximizing action plans, improving human resource capabilities in BARENLITBANG, and optimizing internal control task force.